The Application of Nanotechnology-Based Liquid Organic Fertilizer for Improving the Quality of Hydroponically Grown Vegetables - Resti Fevria; Abdul Razak; Vauzia Vauzia; Santi Diana Putri; Silvy Annisa (Green Engineering Society, 2025)
Hydroponics, a farming technique using nutrient-enriched water, has been widely practiced due to its suitability for limited agricultural land. One of the key factors affecting hydroponic efficiency is the nutrient blend, with AB Mix and liquid organic fertilizer playing a crucial role. This study aims to evaluate the potential of nanotechnology-based nutrient solution in hydroponic to enhance nutrient absorption and improve plant growth in different vegetable species. Five vegetable species, which include red lettuce, red spinach, green spinach, pakcoy, and kailan, were selected to assess the interaction between nutrient composition and vegetable species. A study with factorial design was conducted using a randomized complete block design (RCBD). The primary factor was the fertilizer composition and the secondary factor was the type of vegetable. The treatments consisted of Control (Well water + AB Mix), P1 (Nanotechnology water + 100% AB Mix), P2 (Nanotechnology water + 25% nanotechnology liquid organic fertilizer + 75% AB Mix), P3 (Nanotechnology water + 50% nanotechnology liquid organic fertilizer + 50% AB Mix), P4 (Nanotechnology water + 75% nanotechnology liquid organic fertilizer + 25% AB Mix), and P5 (Nanotechnology water + 100% nanotechnology liquid organic fertilizer). Growth parameters measured included plant height, fresh weight, dry weight, number of leaves, and leaf area. Data were evaluated using a two-way ANOVA to assess the effects of fertilizer composition and vegetable type, followed by a 5% DMRT test for mean comparison. The findings indicated that the use of liquid organic fertilizer technology influenced plant growth. The most optimal average growth was recorded in the P2 treatment (a combination of nanotechnology water, 25% nanotechnology liquid organic fertilizer, and 75% AB Mix), while the least favorable result was observed in P5 (nanotechnology water combined with 100% nanotechnology liquid organic fertilizer).